Determinants of maternal near miss events: a facility based case-control study - Kurugodiyavar, Mahesh D.; Andanigoudar, Kashavva B.; Bant, Dattatreya D.; Nekar, Manjunath S. (International Journal Of Community Medicine And Public Health, 2019)
Background: Worldwide, approximately 830 women died every single day due to complications during pregnancy or childbirth in 2015. Many researchers revealed that the quality of health care delivery in a system can be identified by studies on maternal deaths. In recent years, women who survived the critical events during pregnancy and childbirth, called as maternal near miss cases, are explored as an adjunct to maternal death inquiries, as these cases occur more frequently than maternal deaths and can identify problems that had to be overcome for the provision of better healthcare services. This study aims at evaluating determinants of such maternal near miss events among postnatal women admitted in KIMS Hospital, Hubli. Methods: A case-control study was done on postnatal women admitted in the KIMS Hospital. A structured pre-tested questionnaire was administered to 82 participants (27 cases and 55 controls). Information about biodata, sociodemographic characteristics, medical illnesses, previous pregnancies and the current pregnancy with its outcomes and complications was collected. Results: Most women were satisfying the criterion for admission to ICU followed by hypertensive complications and severe anemia, to be considered as cases. The study showed height, type of family, religion, presence of danger signs during pregnancy as significant determinants of maternal near miss events. Conclusions: The factors showing significance in our study are non-modifiable risk factors of maternal near miss events. With early identification of such cases and appropriate antenatal care, such events can be prevented and reduced.